A study on the design of a hybrid policy for carbon abatement. Issue 1 (2nd January 2017) - Zhang, Bo; He, Mingyang; Pan, Haoran
ABSTRACT: A necessary way to mitigate global warming is carbon reduction, which the international community is now actively promoting. China has committed a target goal for carbon reduction to the international society, and has devoted a great effort toward researching the impact of related policies. Carbon taxation and carbon trading are the two main mechanisms to advocate carbon abatement, which many countries have been using. Each of these two mechanisms possesses advantages and disadvantages, and an appropriate combination of them can make best use of their advantages while bypassing their disadvantages, creating a superior mechanism. In our opinion, the main differences between these two mechanisms are that carbon taxation has a lower institution cost (consisting of the related infrastructural investment and the regulation cost, etc), and is easier to operate, but lacks the flexibility in response to variations of market conditions. However, this flexibility is just the origin of risk, which increases the difficulty for firms in their decision of carbon abatement and is an indirect way to incentivize carbon abatement, compared to carbon trading, which has a more direct effect in carbon reduction. Based on the above observation, we present a hybrid mechanism of carbon abatement, which is an organized combination of carbon taxation and carbon trading. It consists of two parts: first, the carbon taxation, which has a progressive tax rate, second, the carbon trading. Small firms will only pay the carbon tax, while large firms, will first need to get the initial carbon emission quotas by some way, and then trade it in the carbon market if necessary. For firms with extra emissions, they will receive a punishment according to a high carbon tax rate. This hybrid policy considers the equity between different firms in carbon emission rights as well as the efficiency of the mechanism while decreasing the risk level for firms in the carbon emission decision, making it superior to the two previous policies. We also analyze the feasibility of this hybrid policy in China, address some important issues in the implementation of this hybrid policy in China and present the relevant suggestions. The discussion in this paper can serve as a reference to the government in the decision of carbon policies.